2018
DOI: 10.1016/j.eururo.2018.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Magnetic Resonance Imaging for Bladder Cancer: Development of VI-RADS (Vesical Imaging-Reporting And Data System)

Abstract: Magnetic resonance imaging (MRI) scans for bladder cancer are becoming more common and may provide accurate information that helps improve patient care. Here, we describe a standardized reporting criterion for bladder MRI. This should improve communication between doctors and allow better comparisons between patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
355
0
33

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 470 publications
(451 citation statements)
references
References 86 publications
(120 reference statements)
7
355
0
33
Order By: Relevance
“…6 Therefore, preoperative prediction of the recurrence risk in TFTY after operation is very crucial for individualized follow-up strategies of BCa patients. Previous studies 14,15,25,34 have indicated that: 1) postoperative DW and DCE images were capable of identifying tumor recurrence from chronic inflammation and fibrosis after TURBT or cystectomy, 2) mpMRI, including T 2 W, DW, ADC, and DCE images, might be a complementary and potential alternative of cystoscopy for posttreatment follow-up and recurrence surveillance. Whether the preoperative mpMRI with the radiomics strategy is capable of predicting BCa recurrence remains unknown to now.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Therefore, preoperative prediction of the recurrence risk in TFTY after operation is very crucial for individualized follow-up strategies of BCa patients. Previous studies 14,15,25,34 have indicated that: 1) postoperative DW and DCE images were capable of identifying tumor recurrence from chronic inflammation and fibrosis after TURBT or cystectomy, 2) mpMRI, including T 2 W, DW, ADC, and DCE images, might be a complementary and potential alternative of cystoscopy for posttreatment follow-up and recurrence surveillance. Whether the preoperative mpMRI with the radiomics strategy is capable of predicting BCa recurrence remains unknown to now.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings above, we hypothesized that: 1) the radiomics features extracted from preoperative mpMRI to characterize the subtle variations of tissue distribution within the lesion might be potential in predicting BCa recurrence; 2) the combination of the radiomics strategy with important clinical factors, mainly including age, gender, histological grade, and MIS of the archived tumor with the maximal size in bladder lumen, tumor size, NoT, operation choice, together with the imaging signs like stalk and SLE, might add the incremental value for TFTY BCa prediction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although several articles exists supporting the role of mpMRI in patients with bladder cancer [10,11], the first description of the VI-RADS score was performed by Panebianco et al [3] in 2018. A multidisciplinary team composed of members from Europe, North America, South America and Asia with a Delphi-like consensus protocol proposed a 5-point score.…”
Section: The Development Of Vi-radsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) techniques have currently shown potential in determining tumor locations and characteristics in a noninvasive manner . Quantitative characterization of these images to build the associated bridge between image signatures and cancer properties, ie, radiomics, has attracted increasing attention .…”
mentioning
confidence: 99%